2001
DOI: 10.1055/s-2001-15088
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Common Bile-Duct Dilatation in Patients without Biliary Symptoms or Causative Lesions on Ultrasonography

Abstract: We detected a significant number of causative biliary tract lesions in asymptomatic adults with dilatation of the CBD on routine abdominal US; no laboratory or demographic parameters were useful for discrimination. Further diagnostic study will be helpful for the early diagnosis of biliary tract disease in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 6 publications
(6 reference statements)
0
23
0
Order By: Relevance
“…A diameter greater than 7 mm defines CBD dilatation, which may indicate biliary pathology [1][2][3][4] and generally warrants further investigation. Since its inception in the early 1970s, endoscopic retrograde cholangiopancreatography (ERCP) had been regarded as the gold standard for evaluation of the CBD and the biliary tree [5,6].…”
Section: Introductionmentioning
confidence: 98%
“…A diameter greater than 7 mm defines CBD dilatation, which may indicate biliary pathology [1][2][3][4] and generally warrants further investigation. Since its inception in the early 1970s, endoscopic retrograde cholangiopancreatography (ERCP) had been regarded as the gold standard for evaluation of the CBD and the biliary tree [5,6].…”
Section: Introductionmentioning
confidence: 98%
“…[8][9][10] The etiology of a patient's dilated duct can be explored with further investigation via MRCP, EUS or ERCP. 11,12 In the majority of cases, the etiology for the dilated duct(s) is benign but clinicians are always concerned for an underlying neoplasm. 12 Agarwal et al reported that 11.5% of patients who were found to have a dilated pancreatic duct on abdominal imaging had a pancreatic adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…A study in 2001 by Kim et al [42] evaluated patients with asymptomatic biliary dilatation initially identified on US with ERCP, repeat US, or CT. It is unclear, however, what led to the initial imaging that identified the biliary dilatation, and the degree of dilatation is not specified for the entire population but was rather reported as means for subgroups of those patients in whom a plausible causative lesion was identified or no lesion identified (13.2±3.9 mm and 10.7±2.0 mm respectively).…”
Section: Investigation and Managementmentioning
confidence: 99%